Gestión administrativa y financiera y su relación con la calidad de los servicios de la cooperativa cafetalera de producción y mercadeo Chacarita, cantón Ventanas, año 2014 - Vera Guzmán, Kerly Aracely (2016)
This research called administrative and financial management and its relationship with the quality of services the Cooperative Coffee Production and Marketing Chacarita, Canton Ventanas, 2014, focuses primarily on providing quality service to all customers are there specifically the farmer, who is the engine that organization exists because of the service that this requires multiples such as dried rice, corn, cocoa, in order that the client can meet your need the cooperative. Seeking to solve the following research questions the issue as raised: How the administrative and financial management influences the quality of service of the Coffee Production Cooperative Marketing Purchase and Chacarita, this leads to the formulation of objectives; 1. Conduct a situational analysis at the Coffee Production and Marketing Cooperative Chacarita. 2. Examine the economic and financial results and their impact on service quality. 3. Measure the quality of service of the Coffee Production and Marketing Cooperative Chacarita. For structuring the framework was taken as reference the main variables of the objectives, as is administrative, situational, financial analysis, quality of services. It was also used in the methodological part, different methods such as; inductive and deductive, in the kind of research the field research was used, and the literature, interviews the manager and accountant is conducted to know the different points of view of the cooperative, and also He applied a customer survey of the cooperative, here no statistical formula applied since it required only performing simple random sampling, considering that the universe is finite. In conclusion the company needs restructuring the inside according to the interview I gave the manager and accountant of it.